If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5a + -9 = 4a + 5 Reorder the terms: -9 + 0.5a = 4a + 5 Reorder the terms: -9 + 0.5a = 5 + 4a Solving -9 + 0.5a = 5 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. -9 + 0.5a + -4a = 5 + 4a + -4a Combine like terms: 0.5a + -4a = -3.5a -9 + -3.5a = 5 + 4a + -4a Combine like terms: 4a + -4a = 0 -9 + -3.5a = 5 + 0 -9 + -3.5a = 5 Add '9' to each side of the equation. -9 + 9 + -3.5a = 5 + 9 Combine like terms: -9 + 9 = 0 0 + -3.5a = 5 + 9 -3.5a = 5 + 9 Combine like terms: 5 + 9 = 14 -3.5a = 14 Divide each side by '-3.5'. a = -4 Simplifying a = -4
| 10x+5(x-5)=15 | | 2x^2+x^2-176=0 | | t^6+1t^3=42 | | -9+3v=6(6v+4) | | 5p-1-6p=8 | | 12-2a=10 | | -1-x-7x=-1 | | 8(2+4)=5(13+z) | | 5x-6=129 | | 6w= | | 5x-2=3+x+5 | | 1+33d+20+1+12=38 | | 14+3p=20 | | 2-3(x-7)=-1 | | 1+33d+20-1-12=38 | | -2a+24+8a=4a-6a | | 6z-13-z+3=0 | | 3/4t=-48 | | 12/-4/9 | | 4y+2y=5y-2 | | 2(4x-8)+6(5x+2)=6(4x+9)3 | | 3a^2-8a-24a+64= | | 9+m/=2 | | 6x-9+4x=51 | | -1-5x=-26 | | 5(5y-4)-8y= | | 2x^2-6x-2ax+8+a^2=x-1 | | x^3-37x+84=0 | | 80+60+x+51=180 | | (3x-1)-3(2x+3)+42=2x(-x-5)-(x-1) | | 6x+x-6=6x+4 | | 6w-4+4=-3+3+4 |